Biocultural Drivers Responsible for the Occurrence of a Cassava Bacterial Pathogen in Small-Scale Farms of Colombian Caribbean - Pérez, Darío; Duputié, Anne; Vernière, Christian; Szurek, Boris; Caillon, Sophie (Frontiers in Ecology and Evolution, 2022)
Cassava (Manihot esculenta Crantz) is a primary crop for food security of millions of people worldwide. In Colombia, the Caribbean region contributes about half of the national cassava production, despite major socioeconomic constraints such as unequal land property, omnipresence of middlemen, low and unstable prices, armed conflict, climate change and phytosanitary issues. Among the latter is Cassava Bacterial Blight (CBB), a disease caused by the bacterial pathogen Xanthomonas phaseoli pv. manihotis (Xpm) that leads to irreversible damage to plants, impeding growth and productivity. In 2016, we analyzed the role of sociocultural and agricultural practices on CBB prevalence in small-scale fields of a village of the Colombian Caribbean region, where farmers live almost exclusively from the sale of their cassava production. Semi-structured interviews (48) were conducted with all farmers who cultivated cassava to document individual sociodemographic characteristics, cassava farming practices, and perceptions about CBB occurrence. CBB was diagnosed in the field and the presence of Xpm was further confirmed upon laboratory analysis of collected diseased leaf samples. Our data show that i) according to the risks perceived by farmers, CBB is the main disease affecting cassava crops in the village and it could indeed be detected in about half of the fields visited; ii) CBB occurrence depends strongly on land property issues, likely because of an inadequate phytosanitary control during acquisition of cuttings when farmers are forced to rent the land; and iii) there is a strong positive correlation between the use of commercial fertilizers and the occurrence of CBB in the village of Villa López.